Penerapan Metode Logarithmic Percentage Change-Driven Objective Weighting dan Multi-Attribute Utility Theory dalam Penerimaan Guru Bahasa Inggris - Setiawansyah Setiawansyah; Ari Sulistiyawati (PT. Tech Cart Press, 2024)
The admission of English teachers in private schools is an important process in ensuring the quality of education in the institution. This process involves several stages, from the announcement of job vacancies to the selection of candidates who match the established criteria. Problems in the recruitment of English teachers, namely a selection process that lacks transparency or inadequate evaluation tools, can also be an obstacle. Therefore, addressing the problem of English teacher recruitment requires a holistic approach that pays attention to various aspects, including the development of effective recruitment strategies, the provision of training to improve candidate qualifications, and the improvement of the overall selection process. The research objective of applying the LOPCOW (Logarithmic Percentage Change-Driven Objective) Weighting and MAUT (Multi-Attribute Utility Theory) method is to provide a comprehensive and effective framework in the selection process, where LOPCOW is used to analyze objective data related to teacher performance and qualifications, while MAUT is used to integrate the subjective preferences of stakeholders such as principals and school committees in decision making. Thus, the main objective is to optimize the admission process of English teachers by considering these two aspects holistically. The ranking results show that the final results of English teacher admissions recommend the first rank with a final score of 0.7421 obtained by HR Teacher Candidates. This result is the application of the LOPCOW and MAUT methods in the selection process for English teacher admission, and becomes a recommendation for the English teacher admission process.